O-Methyl m-Tolylcarbamothioate - Yeo, Chien Ing *; Tiekink, Edward R. T. * (MDPi, 2018)
The synthesis, spectroscopic, and crystallographic characterisation of the title compound,O-methyl m-tolylcarbamothioate, MeOC(=S)N(H)(m-tolyl) (1), are described. The crystallographic study confirms the structure determined by spectroscopy and shows the presence of the thioamide tautomer, a syn-disposition of the thione-S and thioamide-N-H atoms and, in the crystal, thioamide-N-H . . . S(thione) hydrogen bonding leading to an eight-membered { . . . HNCS}2 synthon.